2019
DOI: 10.17220/ijpes.2019.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Facebook Usage and Depressıon Levels of Selected Filipino College Students

Abstract: This study examined the relationship of sociodemographic characteristics and Facebook usage to the depression level of college students. A total of 347 respondents were purposively selected and completed a self-administered questionnaire. Results showed that: sex has a weak positive association with depression level (r=0.0962); age did not vary much across depression level; there is a moderate positive association between sexual orientation and depression level (r= 0.2794); socioeconomic status has an inverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Further work is needed to identify the negative consequences of prolonged quarantine on individuals, especially those who have preexisting mental health problems and those who experience a disruption in access to their mental health-care providers. Moreover Odacı and Kalkan (2010) reported that internet use, specifically social media ( Maglunog and Dy, 2019 ) exacerbates loneliness and that social media usage is expected to rise during the ECQ. Another important question, therefore, is how does the ongoing quarantine affects rates and levels of loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…Further work is needed to identify the negative consequences of prolonged quarantine on individuals, especially those who have preexisting mental health problems and those who experience a disruption in access to their mental health-care providers. Moreover Odacı and Kalkan (2010) reported that internet use, specifically social media ( Maglunog and Dy, 2019 ) exacerbates loneliness and that social media usage is expected to rise during the ECQ. Another important question, therefore, is how does the ongoing quarantine affects rates and levels of loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…Low self-control online is associated with aggression offline (Hameed & Irfan, 2021), and patterns of maladaptive behaviors online are associated with increased psychopathology (Smith et al, 2013;Wright et al, 2018). Accordingly, these findings provide insight for intervening on problematic online behaviors that are associated with poor relationships, personality disorders, mood disorders, and anxiety (e.g., Labrague, 2014; Maglunog & Dy, 2019;Rosen et al, 2013;Tandoc et al, 2015). For example, prior work demonstrates that practicing self-control in one domain, such as in spending and financial decisions or in exercising regularly, can not only lead to improvements in that one domain but in others as well (Oaten & Cheng, 2006.…”
Section: Discussionmentioning
confidence: 94%
“…Bullying or meanness as type of perceived negative Facebook experience (Rosenthal et al, 2016), misunderstandings as type of perceived negative Facebook experience (Rosenthal et al, 2016), number of Facebook friends (Rosen et al, 2013a;Rae and Lonborg, 2015;Brailovskaia and Margraf, 2019), number of physical locations which a user has tagged on Facebook (Park et al, 2013), perceived negative Facebook experience (Rosenthal et al, 2016), perceived social comparison when using Facebook actively (Nisar et al, 2019), perceived social connectedness from the use of Facebook (Grieve et al, 2013), perceived social support on Facebook (Zhang, 2017), perceived social support through Facebook Eggermont, 2015, 2016a;Frison et al, 2019), perceived upward-identification in social comparison on Facebook (Kang et al, 2013), relationship maintenance as motive for using Facebook (Scherr and Brunet, 2017), and unwanted contact as type of perceived negative Facebook experience (Rosenthal et al, 2016) No Effects Academic motive for using Facebook (Koc and Gulyagci, 2013), active Facebook use (Simoncic et al, 2014;Hanna et al, 2017;Dibb and Foster, 2021), active posting on Facebook (große Deters and Mehl, 2013), active private Facebook use (Frison and Eggermont, 2016a), commenting as motive for using Facebook (Maglunog and Dy, 2019), creating or RSVPing to events as motive for using Facebook (Maglunog and Dy, 2019), daily Facebook use (Simoncic et al, 2014;Brailovskaia et al, 2019b), daily informational motive for using Facebook (Koc and Gulyagci, 2013), entertainment/distraction as motive for using…”
Section: Effectsmentioning
confidence: 99%